Clinical features and risk factors of immune-mediated liver injury in non-small cell lung cancer patients treated with immune checkpoint inhibitors - Yang, Ling; Zhuo, Chao; Li, Chonghuan; Liu, Yujing; Liu, Xinyi; Huang, Yibin; Wu, Bingbing; Su, Jiawei (Frontiers in Oncology, 2025)
PurposeThis study investigated the clinical features, risk factors, and recurrence of immune-mediated liver injury (IMLI) in non-small cell lung cancer (NSCLC) patients treated with immune checkpoint inhibitors (ICIs).MethodsA retrospective cohort of 274 NSCLC patients receiving ICIs was analyzed. Baseline inflammatory markers, including white blood cell count (WBC), albumin levels, and prognostic nutritional index (PNI), were assessed for their association with IMLI. Risk factors were identified using logistic regression, and recurrence outcomes were analyzed.ResultsIMLI incidence was 35.4%, with 15.5% of cases classified as grade 3-4. WBC ≤11.0×109/L (P<0.001) and albumin ≥35 g/L (P<0.001) were independent predictors of IMLI. Among patients with IMLI, 28.9% experienced recurrence, with 17.9% classified as grade 3-4. Recurrence risk was not significantly higher than the initial onset (P=0.21).ConclusionLow baseline inflammatory status predicts IMLI in NSCLC patients undergoing ICI therapy. Monitoring baseline inflammatory markers can guide risk stratification, and re-challenging ICIs in selected patients appears feasible without significantly increasing recurrence risk.